Weight Training Pada Otot Lengan di Olaharaga Panahan - Bernhardin, Dindin (STKIP Pasundan, 2022)
The purpose of this study is to find out the impact of the intensity of weight training (bench press and lateral full down) in increasing arm muscle strength in the drawing technique of archery. The research method used in this study is the experimental method, research instrument or data collection tool used in this study is a 30 meter archery test. The population and sample used in this study are students who are members of the Pasundan Cimahi Archery Student Activity Unit (STKIP). The calculation results show t = 6,703, p = 0,000 means significant. This means that the intensity of weight training exercises (bench press and lateral full down) has a significant effect on increasing arm muscle strength in drawing techniques in archery. The mean for the initial test and the final test shows a positive difference.